-9.3x+1.2=3.8-8.3x

Simple and best practice solution for -9.3x+1.2=3.8-8.3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9.3x+1.2=3.8-8.3x equation:


Simplifying
-9.3x + 1.2 = 3.8 + -8.3x

Reorder the terms:
1.2 + -9.3x = 3.8 + -8.3x

Solving
1.2 + -9.3x = 3.8 + -8.3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8.3x' to each side of the equation.
1.2 + -9.3x + 8.3x = 3.8 + -8.3x + 8.3x

Combine like terms: -9.3x + 8.3x = -1x
1.2 + -1x = 3.8 + -8.3x + 8.3x

Combine like terms: -8.3x + 8.3x = 0.0
1.2 + -1x = 3.8 + 0.0
1.2 + -1x = 3.8

Add '-1.2' to each side of the equation.
1.2 + -1.2 + -1x = 3.8 + -1.2

Combine like terms: 1.2 + -1.2 = 0.0
0.0 + -1x = 3.8 + -1.2
-1x = 3.8 + -1.2

Combine like terms: 3.8 + -1.2 = 2.6
-1x = 2.6

Divide each side by '-1'.
x = -2.6

Simplifying
x = -2.6

See similar equations:

| 3(2x-5)+4x=7x+2 | | (3x+56y)(12x-5y)=0 | | 6+1=4x+5 | | 3.3x+7.3=9.4+2.7x | | lx-3l+lx-11l=8 | | 8x+5=15+3x | | 7x^2+12y^2= | | 7x+9=39+2x | | 7x+9=39+2z | | -3.6x-6.9-8x=-5.5 | | (9y+18)+(5x+x)=90 | | 9(4w-8)=12(3w+5) | | 2(3x-4)-12=(5x-3) | | 9y+18+5x+x=90 | | 9x+5+3x+1=90 | | Y=a+bx+cx^2+dx^3 | | 8x+6y=450 | | 2x+14=20-4x | | -30=5y-5 | | 8x+16=106-2x | | 21-7x=39-10x | | (4w+3)*2w=9w | | -17m-11=-9m-59 | | 7x+9=29-3x | | 3x+8=38-2x | | x-2+3=12 | | 3(2x+1)-4(x-2)=25 | | f(x)=-3x^2+15 | | 5*5+7-3= | | 110=w(w+15) | | W^2+15w=110 | | 4xy-4xz= |

Equations solver categories